Flashes and floaters. Issue 5 (May 2014) - Newsom, Richard; Simon, Chantal
Patients commonly present to GPs because they have seen flashing lights in their visual fields. These symptoms can reflect long-standing degenerative processes or can be caused by acute sight- threatening eye disease or occasionally neurological disease. 'Floaters' are seen as dots or spots that 'float' in front of everything looked at by the person. They may occur alone or in association with flashes. This article aims to provide GPs with a strategy to separate those patients with flashes and/or floaters who simply require reassurance, from those who require referral to eye casualty or for neurological assessment.